2007
DOI: 10.1161/01.str.0000254128.05122.a2
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Arterial Thrombolysis for Basilar Artery Thrombosis

William J. Powers

Abstract: Abstract-The poor prognosis for recovery of basilar artery thrombosis has led to the adoption at many institutions of intra-arterial thrombolysis as part of clinical care. However, because neither randomized clinical trials nor observational data provide evidence for treatment efficacy and there are substantial risks and costs associated with this procedure, this treatment should only be performed in the context of a randomized, controlled clinical trial subject to appropriate Institutional Review Board review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…Even among the BAO patients, the outcome was much better than previously assumed [22]. Furthermore, several studies based on the OCSP classification suggested the total AC infarcts had the poorest outcome [16,23,24,25,26]. As little information exists in previous studies for the long-term outcome after PCI, further comparison is limited.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Even among the BAO patients, the outcome was much better than previously assumed [22]. Furthermore, several studies based on the OCSP classification suggested the total AC infarcts had the poorest outcome [16,23,24,25,26]. As little information exists in previous studies for the long-term outcome after PCI, further comparison is limited.…”
Section: Discussionmentioning
confidence: 94%
“…The poor outcome for PCI has been proposed in earlier studies [13,14,15,16,17,18,19,20]. Some were necropsy studies or involved only a small number of patients in specifically PC lesions or selected patients with more severe stroke focusing on basilar artery intraarterial thrombolysis.…”
Section: Discussionmentioning
confidence: 99%
“…2 Since then, an open discussion among specialists has begun on whether to treat patients with BAO intraarterially or intravenously and whether a randomized controlled trial is feasible. [13][14][15][16][17][18][19][20][21] In a multicenter observational study it has recently been shown that the bridging concept, using combined treatment with IA rt-PA and IV platelet glycoprotein IIb/IIIa receptor inhibitors and additional percutaneous transluminal angioplasty/stenting in case of severe residual stenosis after IAT, might improve neurological outcome compared to IAT with rt-PA alone. 9 In this monocenter retrospective analysis, we compared the treatment of acute BAO with IAT alone and the combined approach of an IV glycoprotein IIb/IIIa inhibitor plus IA rt-PA treatment (bridging).…”
Section: Discussionmentioning
confidence: 99%
“…Critics of IAT claim that procedural risks and expenses cannot currently be justified 33. Proponents suggest higher rates of recanalization with IAT and potentially lower rates of symptomatic intracranial hemorrhage 1 4 5.…”
Section: Iat Versus Ivt: Some Controversial Findingsmentioning
confidence: 99%